Magic components—why quantifying rain, snowmelt, and icemelt in river discharge is not easy. Issue 1 (23rd November 2017) - Weiler, Markus; Seibert, Jan; Stahl, Kerstin
Abstract: Quantifying the components of rain, snowmelt, and glacier ice melt in river discharge is an important but difficult task in hydrology. Although it forms the basis of many climate impact assessments, many published modelling results do not clearly describe how they derived the discharge components. Consequently, reported components such as absolute amounts or relative percentages of snow and ice melt from different studies are rarely comparable. This commentary revisits the differences in the terminology used, the modelling approaches, and the possible conclusions for effects at different time scales. We argue that for questions related to changes in discharge, not particle tracking, for which methodology is widely available, but instead, an "effect tracking" of the input contributions is important, that is, the representation of the signals of rainfall, snowmelt, and glacier ice melt in the discharge at the catchment outlet. We introduce and briefly describe a method for effect tracking and discuss the differences and advantages compared to other methods. This comparison supports our call to the modelling community for more precise descriptions of how the generated input contributions into a catchment from rainfall, snowmelt, and glacier ice melt are tracked through the catchments' multiple stores to finally compose the presented hydrographs.